PENERAPAN MODEL PEMBELAJARAN INVESTIGASI KELOMPOK DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI KELAS VIII SMP NEGERI 1 LUAHAGUNDRE MANIAMOLO TAHUN PELAJARAN 2022/2023 - Ge'e, Takwim (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2023)
Choosing the right learning model will have an impact on a student's academic success and achievement of learning goals. The objective of the study was to determine the extent to which students' sociological learning outcomes were increased through the application of group inquiry learning models. The type of research used is classroom activity research (PTK). Research tools in the form of student achievement tests, worksheets, and documents. Subjects of the study are grade VIII students, a total of 28 students. Result:at first cycle is 60.71 n, second cycle reaches 100%. The average score in the first cycle was 62.50 and increased in the second cycle to 80. An increase in the average percentage of completed academic results helps to meet the school action success criterion ≥ 75%. Conclusion of the study:The application of the group learning model can improve the academic performance of sociology students in grade VIII SMP Negeri 1 Luahagundre Maniamolo in the 2022/2023 school year. Suggest:For teachers, when learning, teachers should apply a group learning model in each subject, because this model can stimulate students to interact and exchange ideas directly. Students should be more actively involved in learning, both individually and in groups. It is hoped that other researchers can become a source of ideas to conduct similar studies, as a topic to improve the quality of research results and enrich the knowledge of researchers. to identify appropriate learning models.